Unveiling determinant of student engagement - Gustina Siregar; Lila Bismala; Hafsah Hafsah; Susi Handayani; Yayuk Hayulina Manurung; Dewi Andriany; Lailan Safina Hasibuan (Intelektual Pustaka Media Utama, 2023)
The purpose of this study was to examine the moderating role of feedback in the influence between lecturer leadership, lecturer engagement, and student engagement. The study was conducted on students at the Universitas Muhammadiyah Sumatera Utara, Indonesia where the number of respondents who filled out the questionnaire was 231 respondents. With structural equation modeling, using SemPLS, a moderation test was conducted to prove the research hypothesis that had been designed. The results of the study show that although feedback affects student engagement, feedback does not act as a moderator in the influence between lecturer leadership, lecturer engagement, and student engagement. Meanwhile, lecturer engagement was found not to affect student engagement, but lecturer engagement significantly affected student engagement. In learning, lecturers must pay attention to feedback and lecturer leadership, if lecturers expect high student engagement. This has implications that lecturers have to provide feedback and practice lecturer leadership in the classroom.